2014
DOI: 10.1063/1.4883918
|View full text |Cite
|
Sign up to set email alerts
|

Laser scattered images observed from carbon plasma stagnation and following molecular formation

Abstract: Two carbon targets were irradiated to create plasma plumes to collide at right angle with two UV laser pulses each other at 10 J/cm2/pulse. The collision results in carbon plasma stagnation. Laser scattered imaging indicates that the carbon large molecular formation takes place much later in time after the laser irradiation and stagnation. Compared with the temporal history of electron density (ne), ion density (ni), and plasma self-emission dominated by carbon Swan band, it is estimated that the carbon large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the case of hard stagnation, rapid accumulation of plasma material at the collision front leads to the formation of a dense layer of material between the two plasmas called stagnation layer [1]. The study of properties of stagnation layer has attracted the curiosity of researchers for the past four decades because of its broad range of applications in various fields of science such as inertial confinement fusion [2], laser induced breakdown spectroscopy [3], pulsed laser deposition [4], EUV lithography [5], understanding the formation of supernovae and its remnants [6] etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hard stagnation, rapid accumulation of plasma material at the collision front leads to the formation of a dense layer of material between the two plasmas called stagnation layer [1]. The study of properties of stagnation layer has attracted the curiosity of researchers for the past four decades because of its broad range of applications in various fields of science such as inertial confinement fusion [2], laser induced breakdown spectroscopy [3], pulsed laser deposition [4], EUV lithography [5], understanding the formation of supernovae and its remnants [6] etc.…”
Section: Introductionmentioning
confidence: 99%
“…3237 St-Onge et al 38 demonstrated that C 2 and C are released directly from the target of the graphite and that CN is formed later on by the interaction of C 2 with atmospheric nitrogen (N 2 ). Nishimura et al 39 established that large C molecular formation is initiated with the ion collision, followed by the formation of C 2 . The formation of CN molecular species also results from reactions between native C atoms and nitrogen present in ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…One of the recent applications of colliding plumes is to simulate the fusion reactor chamber environment. 10 Laser induced colliding plasmas also find applications in inertial confinement fusion, x-ray lasers, and understanding the formation of super novae and its remnants. [11][12][13][14] Single plasma plumes have been investigated extensively using different experimental and theoretical techniques.…”
mentioning
confidence: 99%